2016
DOI: 10.1103/physrevb.94.024436
|View full text |Cite
|
Sign up to set email alerts
|

Candidate quantum spin ice in the pyrochlorePr2Hf2O7

Abstract: Copies of full items can be used for personal research or study, educational, or not-for-profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. Publisher statement: © 2016 American Physical Society A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
80
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 49 publications
24
80
0
Order By: Relevance
“…The Pr 3+ effective moment is estimated to be µ eff = 2.51(1)µ B , a similar value to the one found in Pr 2 Zr 2 O 7 [27,39]. The calculated values of the CurieWeiss temperature θ W , and of the effective moment µ eff are in agreement with those determined by detailed investigations of the low temperature magnetic properties of our Pr 2 Hf 2 O 7 crystals [57]. We note the apparent discrepancy between the negative CurieWeiss temperature and the fact that the physics of Pr-based pyrochlores appears to be related to spin ice [27,57,59].…”
Section: Magnetic Propertiessupporting
confidence: 78%
See 2 more Smart Citations
“…The Pr 3+ effective moment is estimated to be µ eff = 2.51(1)µ B , a similar value to the one found in Pr 2 Zr 2 O 7 [27,39]. The calculated values of the CurieWeiss temperature θ W , and of the effective moment µ eff are in agreement with those determined by detailed investigations of the low temperature magnetic properties of our Pr 2 Hf 2 O 7 crystals [57]. We note the apparent discrepancy between the negative CurieWeiss temperature and the fact that the physics of Pr-based pyrochlores appears to be related to spin ice [27,57,59].…”
Section: Magnetic Propertiessupporting
confidence: 78%
“…In Pr 2 Hf 2 O 7 the magnetization response is temperature dependent (see Figs. 6(a)-(f)), with the strongly anisotropic response only observed below about 10 K. Finally, we note the absence of evidence for a magnetization plateau developing in the M (H) curve when the field is applied along the [111] direction, as opposed to observations made at much lower temperature [57]. The discrepancy only arises from the difference in temperature, because ferromagnetic correlations only develop below 0.5 K in this system [57].…”
Section: Magnetic Propertiesmentioning
confidence: 59%
See 1 more Smart Citation
“…These results were interpreted as the evidence of quantum dynamics in a new class of spin ice system. Nevertheless, in Pr 2 Zr 2 O 7 and Pr 2 Hf 2 O 7 the Curie-Weiss temperature inferred from magnetic susceptibility is negative [21][22][23]25], thus indicating antiferromagnetic interactions, which is a priori not consistent with the spin ice picture. In addition, the fact that most of the neutron scattering signal in Pr 2 Zr 2 O 7 has an inelastic character calls for peculiar spin dynamics, different from conventional spin ice.…”
Section: Introductionmentioning
confidence: 72%
“…Recently, several theoretical studies [16][17][18] [24], and more recently Pr 2 Hf 2 O 7 [25] have shown that the Pr 3+ moment has a strong Ising character, described by a non-Kramers magnetic doublet. As in spin ice, no magnetic long-range ordering is observed down to dilution temperature, and magnetic specific heat shows a broad peak at about 2 K [21,22,[24][25][26][27], similar to what is observed in the classical spin ice Dy 2 Ti 2 O 7 .…”
Section: Introductionmentioning
confidence: 99%